Inflammatory activity and intensity of Helicobacter Pylori colonisation in non-erosive antral gastritis - Gürkan BAŞARAN,; Şerife BAŞARAN,; Ali MERT,; Zeynep ALGÜN,; Hakan ŞENTÜRK, (Turkish Journal of Gastroenterology, 2019)
-